2021
DOI: 10.1007/s00122-021-03946-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics prediction of oat agronomic and seed nutritional traits across environments and in distantly related populations

Abstract: Key message Integration of multi-omics data improved prediction accuracies of oat agronomic and seed nutritional traits in multi-environment trials and distantly related populations in addition to the single-environment prediction. Abstract Multi-omics prediction has been shown to be superior to genomic prediction with genome-wide DNA-based genetic markers (G) for predicting phenotypes. However, most of the existing studies were based on historica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…instance, computing relationship matrices from metabolomics data (Campbell et al, 2021a) or metabolomics and transcriptomics data (Hu et al, 2021) led to high mean prediction accuracies (r > 0.4) for fatty acid traits in oat (Avena sativa L.) seed. These studies have demonstrated that genomic prediction is effective for a few to tens of biochemically similar metabolites traits.…”
Section: Core Ideasmentioning
confidence: 99%
See 4 more Smart Citations
“…instance, computing relationship matrices from metabolomics data (Campbell et al, 2021a) or metabolomics and transcriptomics data (Hu et al, 2021) led to high mean prediction accuracies (r > 0.4) for fatty acid traits in oat (Avena sativa L.) seed. These studies have demonstrated that genomic prediction is effective for a few to tens of biochemically similar metabolites traits.…”
Section: Core Ideasmentioning
confidence: 99%
“…Whole-metabolome phenotypes were measured from mature seeds using untargeted LC-MS and GC-MS in a diverse oat germplasm panel of 375 inbred lines (discovery panel). These phenotypes have been previously described (Brzozowski et al, 2021;Campbell et al, 2021aCampbell et al, , 2021bHu et al, 2021). For each metabolite phenotype, measured as relative signal intensity, deregressed best linear unbiased predictors (drBLUPs) could be calculated for 1,067 of the LC-MS and 601 of the GC-MS signals as in Campbell et al (2021b).…”
Section: Oat Metabolome Discovery Phenotypesmentioning
confidence: 99%
See 3 more Smart Citations